The Effect of The Baamboozle-Assisted Group Investigation (GI) Learning Model on Elementary School Students' Mathematical Understanding - Indriani, Rina; Yusliani, Hany; Nurhadi, Moh (IJORER : International Journal of Recent Educational Research, 2026)
Objective: This research was motivated by the problem of the low mathematical understanding skills in elementary school students. The study aimed to analyze the influence and the effect of implementing the Group Investigation (GI) cooperative learning model assisted by baamboozle media on elementary school students' mathematical understanding abilities of elementary school students, specifically concerning the topic of standard unit volume. Method: The research targeted fourth-grade students at SDN 066 Halimun, Bandung City, as the research population. Class IV D was the experimental group and Class IV A the control, chosen by purposive sampling. A quasi-experimental research method with a nonequivalent control group design was employed. Data were collected through tests, observations, interviews, and documentation. For data analysis, IBM SPSS Statistics 29.0 software was used to conduct normality tests, homogeneity tests, hypothesis tests and and manually calculated effect size tests. Results: Based on the research findings, the mathematical understanding ability profile of students in the experimental group was better than that of the control group, and the experimental group's data was more consistent around the mean. The results of the Mann–Whitney U test showed a significance value (2-tailed) of < 0.001 (p < 0.05), indicating that the Baamboozle-assisted Group Investigation (GI) cooperative learning model had a significant effect on elementary school students' mathematical understanding ability. Furthermore, the effect size test yielded a value of 2.424 (> 0.5), indicating a large effect of the use of the GI learning model and Baamboozle media in improving students' mathematical understanding ability. Novelty: The novelty of this research lies in the strategic integration of the Group Investigation (GI) Cooperative Model with the Baamboozle gamification platform to enhance students' mathematical conceptual understanding.